Calcium Trimetaphosphate-Loaded Electrospun Poly(Ester Urea) Nanofibers for Periodontal Tissue Engineering - Toledo, Priscila T. A. [UNESP]; Anselmi, Caroline [UNESP]; Dal-Fabbro, Renan; Mahmoud, Abdel H.; Abel, Alexandra K.; Becker, Matthew L.; Delbem, Alberto Carlos Botazzo [UNESP]; Bottino, Marco C. (MDPI, 2023)
The objective of this research was to create and appraise biodegradable polymer-based nanofibers containing distinct concentrations of calcium trimetaphosphate (Ca-TMP) for periodontal tissue engineering. Poly(ester urea) (PEU) (5% w/v) solutions containing Ca-TMP (15%, 30%, 45% w/w) were electrospun into fibrous scaffolds. The fibers were evaluated using SEM, EDS, TGA, FTIR, XRD, and mechanical tests. Degradation rate, swelling ratio, and calcium release were also evaluated. Cell/Ca-TMP and cell/scaffold interaction were assessed using stem cells from human exfoliated deciduous teeth (SHEDs) for cell viability, adhesion, and alkaline phosphatase (ALP) activity. Analysis of variance (ANOVA) and post-hoc tests were used (α = 0.05). The PEU and PEU/Ca-TMP-based membranes presented fiber diameters at 469 nm and 414-672 nm, respectively. Chemical characterization attested to the Ca-TMP incorporation into the fibers. Adding Ca-TMP led to higher degradation stability and lower dimensional variation than the pure PEU fibers; however, similar mechanical characteristics were observed. Minimal calcium was released after 21 days of incubation in a lipase-enriched solution. Ca-TMP extracts enhanced cell viability and ALP activity, although no differences were found between the scaffold groups. Overall, Ca-TMP was effectively incorporated into the PEU fibers without compromising the morphological properties but did not promote significant cell function.